Prospective evaluation of vancomycin therapeutic usage and trough levels monitoring - Wissam K Kabbara; Ghada El-Khoury; Nour R Chamas (Journal of Infection in Developing Countries)
Introduction: Vancomycin is the cornerstone of parenteral therapy for serious methicillin resistant Staphylococcus aureus infections. Optimal dosing of vancomycin is patient specific due to its narrow therapeutic window. The objective of this study is to evaluate the appropriate use of vancomycin focusing on the indication, dose, and therapeutic level monitoring.